Fatty acid oxidation is required for the respiration and proliferation of malignant glioma cells. Issue 1 (29th June 2016) - Lin, Hua; Patel, Shaan; Affleck, Valerie S.; Wilson, Ian; Turnbull, Douglass M.; Joshi, Abhijit R.; Maxwell, Ross; Stoll, Elizabeth A.
Abstract: Background: Glioma is the most common form of primary malignant brain tumor in adults, with approximately 4 cases per 100 000 people each year. Gliomas, like many tumors, are thought to primarily metabolize glucose for energy production; however, the reliance upon glycolysis has recently been called into question. In this study, we aimed to identify the metabolic fuel requirements of human glioma cells. Methods: We used database searches and tissue culture resources to evaluate genotype and protein expression, tracked oxygen consumption rates to study metabolic responses to various substrates, performed histochemical techniques and fluorescence-activated cell sorting-based mitotic profiling to study cellular proliferation rates, and employed an animal model of malignant glioma to evaluate a new therapeutic intervention. Results: We observed the presence of enzymes required for fatty acid oxidation within human glioma tissues. In addition, we demonstrated that this metabolic pathway is a major contributor to aerobic respiration in primary-cultured cells isolated from human glioma and grown under serum-free conditions. Moreover, inhibiting fatty acid oxidation reduces proliferative activity in these primary-cultured cells and prolongs survival in a syngeneic mouse model of malignant glioma. Conclusions: Fatty acid oxidation enzymes are present and active within glioma tissues. Targeting this metabolic pathway reduces energy production and cellular proliferation in glioma cells. The drug etomoxir may provide therapeutic benefit to patients with malignant glioma. In addition, the expression of fatty acid oxidation enzymes may provide prognostic indicators for clinical practice.